Evaluating atmospheric CO2 inversions at multiple scales over a highly inventoried agricultural landscape. (12th March 2013) - Schuh, Andrew E.; Lauvaux, Thomas; West, Tristram O.; Denning, A. Scott; Davis, Kenneth J.; Miles, Natasha; Richardson, Scott; Uliasz, Marek; Lokupitiya, Erandathie; Cooley, Daniel; Andrews, Arlyn; Ogle, Stephen
Abstract An intensive regional research campaign was conducted by the North American Carbon Program (NACP) in 2007 to study the carbon cycle of the highly productive agricultural regions of the Midwestern United States. Forty‐five different associated projects were conducted across five US agencies over the course of nearly a decade involving hundreds of researchers. One of the primary objectives of the intensive campaign was to investigate the ability of atmospheric inversion techniques to use highly calibrated CO2 mixing ratio data to estimate CO2 flux over the major croplands of the United States by comparing the results to an inventory of CO2 fluxes. Statistics from densely monitored crop production, consisting primarily of corn and soybeans, provided the backbone of a well studied bottom‐up inventory flux estimate that was used to evaluate the atmospheric inversion results. Estimates were compared to the inventory from three different inversion systems, representing spatial scales varying from high resolution mesoscale (PSU), to continental (CSU) and global (CarbonTracker), coupled to different transport models and optimization techniques. The inversion‐based mean CO2‐C sink estimates were generally slightly larger, 8–20% for PSU, 10–20% for CSU, and 21% for CarbonTracker, but statistically indistinguishable, from the inventory estimate of 135 TgC. While the comparisons show that the MCI region‐wide C sink is robust across inversion system and spatial scale, only the continental and mesoscale inversions were able to reproduce the spatial patterns within the region. In general, the results demonstrate that inversions can recover CO2 fluxes at sub‐regional scales with a relatively high density of CO2 observations and adequate information on atmospheric transport in the region.